1993
DOI: 10.1007/bf03041392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leaf blast on growth and production of a rice crop. 2. Analysis of the reduction in dry matter production, using two models with different complexity

Abstract: Effects of leaf blast on dry matter production of rice observed in a field experiment were analysed in terms of cumulative radiation interception by green foliage (PARCUM; MJm-2 ) and radiation use efficiency (RUE; g dry matter MJ-1 ). Leaf blast caused significant reductions in total dry matter production as a result of a decrease in PARCUM and a decrease in RUE. Reductions in radiation interception (RI; MJm-) and RUE were first observed shortly after the introduction of the disease. RI was significantly redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Since first Striga infection on CK60‐B in 1999 was already observed at 23 DAS, it is suggested that host plants can particularly benefit from delayed infection when first infection occurs early. Previously, such a strong sensitivity to infection time during early growth stages was demonstrated for various fungal leaf pathogens like powdery mildew ( Erysiphe graminis ) and stripe rust ( Puccinia hordei ) on spring barley (Lim & Gaunt, 1986), late blight ( Phytophthora infestans ) on potato (Van Oijen, 1991) and leaf blast ( Magnaporthe grisea ) on rice (Bastiaans, 1993). It is obvious that the consequences of a physiological disturbance following infection will be stronger with smaller host plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since first Striga infection on CK60‐B in 1999 was already observed at 23 DAS, it is suggested that host plants can particularly benefit from delayed infection when first infection occurs early. Previously, such a strong sensitivity to infection time during early growth stages was demonstrated for various fungal leaf pathogens like powdery mildew ( Erysiphe graminis ) and stripe rust ( Puccinia hordei ) on spring barley (Lim & Gaunt, 1986), late blight ( Phytophthora infestans ) on potato (Van Oijen, 1991) and leaf blast ( Magnaporthe grisea ) on rice (Bastiaans, 1993). It is obvious that the consequences of a physiological disturbance following infection will be stronger with smaller host plants.…”
Section: Discussionmentioning
confidence: 99%
“…The feedbacks that are operative in this complex relationship suggest that dynamic simulation models, which have been successfully applied with other host–pest (e.g. Bastiaans, 1993) and crop–weed relationships (e.g. Kropff et al.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, radiation interception was affected, which in turn contributed to the reduction in dry matter production. A more detailed analysis of the reduction in dry matter production will be given in a next paper (Bastiaans, 1993b). Harvest index for both healthy and inoculated crops was about 0.53, a common value for modem rice varieties (Yoshida, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Lucas et al (1998) and Be´asse et al (2000) showed that, when the disease established late, it affected radiation use efficiency (RUE) but had little or no effect on radiation intercepted efficiency (RIE). For other pathosystems, such as late blight/potato (van Oijen, 1991) and leaf blast/rice (Bastiaans, 1993), leaf area formation may be affected due to early growth retardation causing a feedback regulation, and disrupting leaf area formation. For Mp/pea, growth was generally reduced after the beginning of seed filling, and leaf area was no longer expanding at this stage (Be´asse et al, 2000).…”
Section: Introductionmentioning
confidence: 98%